2020
DOI: 10.3390/foods9030322
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Faba Bean Protein Ingredients Produced Using Dry Fractionation and Isoelectric Precipitation: Techno-Functional, Nutritional and Environmental Performance

Abstract: Dry fractionated faba bean protein-rich flour (FPR) produced by milling/air classification, and faba bean protein isolate (FPI) produced by acid extraction/isoelectric precipitation were compared in terms of composition, techno-functional properties, nutritional properties and environmental impacts. FPR had a lower protein content (64.1%, dry matter (DM)) compared to FPI (90.1%, DM), due to the inherent limitations of air classification. Of the two ingredients, FPR demonstrated superior functionality, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
149
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(197 citation statements)
references
References 64 publications
13
149
0
Order By: Relevance
“…A higher number of charges (like dissociated acids) in the system increases intramolecular repulsive forces and therefore promotes the unfolding of gluten proteins which leads to more swelling and higher water absorption [103]. Furthermore, Vogelsang-O'Dwyer et al reported a drastically decreased solubility of faba bean protein between pH 3.6 and 6.0 [18]. Both FB fermentates in the present study exhibit pH values in this range.…”
Section: Water Absorption and Gluten Aggregationsupporting
confidence: 52%
“…A higher number of charges (like dissociated acids) in the system increases intramolecular repulsive forces and therefore promotes the unfolding of gluten proteins which leads to more swelling and higher water absorption [103]. Furthermore, Vogelsang-O'Dwyer et al reported a drastically decreased solubility of faba bean protein between pH 3.6 and 6.0 [18]. Both FB fermentates in the present study exhibit pH values in this range.…”
Section: Water Absorption and Gluten Aggregationsupporting
confidence: 52%
“…To mimic the skim and whole milk Greek yogurt compositions, the plant protein powders of mung bean (MB), chickpea (CP), pea (PP), lentil (LP), and faba bean (FB) were added to water, without and with sunflower oil (SO). A 12% (w/w) protein concentration was fixed for all formulations as it was around the minimum gelation concentration for the plant proteins and enabled comparison between samples [11][12][13][14], while the fat content was approximately 5% (w/w) for samples with sunflower oil. The composition information and labels for all ten formulations and the reference yogurts are shown in Table 1.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Dry fractionation, such as air classification, can be used to create fractions from faba bean that are enriched in protein or starch, as opposed to soy, in which protein is concentrated through a wet process. Dry fractionation is less energy intensive since no water is added, and therefore does not need to be removed, making this process more sustainable and economical [ 8 , 24 ]. Therefore, the protein-rich ingredients are not heated during purification, allowing them to maintain their native state and functionality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the protein-rich ingredients are not heated during purification, allowing them to maintain their native state and functionality [ 8 ]. Dry processed faba bean proteins have a high solubility in water [ 24 ], a low water-holding capacity [ 25 ], and the doughs prepared from faba bean proteins are sticky [ 9 ], making them difficult to handle [ 26 ]. Consequently, the heating step is identified as a potential solution to the low applicability of faba bean protein in meat replacers and possibly other structured food products caused by the less suitable properties for structuring after dry fractionation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation